Development of an object-oriented programming tool based on fem for numerical simulation of mineral-slurry transport - Peralta, S.; Córdova, J.; Celis, C.; Maza, D. (Springer Science and Business Media Deutschland GmbH, 2020)
The early stages of the development of a finite element method (FEM) based computational tool for numerically simulating mineral-slurry transport involving both Newtonian and non-Newtonian flows are described in this work. The rationale behind the conception, design and implementation of the referred object-oriented programming tool is thus initially highlighted. A particular emphasis is put on several architectural aspects accounted for and object class hierarchies defined during the development of the tool. Next one of the main modules composing the tool under development is further described. Finally, as a means of illustration, the use of the FEM based tool for simulating two-dimensional laminar flows is discussed. More specifically, canonical configurations widely studied in the past are firstly accounted for. A more practical application involving the simulation of a mineral-slurry handling device is then studied using the power-law rheological model. The results from the simulations carried out highlight the usefulness of the tool for realistically predicting the associated flow behavior. The FEM based tool discussed in this work will be used in future for carrying out high-fidelity numerical simulations of turbulent multiphase flows including fluid-particle interactions.
Keywords: Finite element method; Computer science; Laminar flow; Object-oriented programming; Turbulence; Mechanical engineering; Computational science; Mechanics; Programming language; Engineering; Structural engineering; Physics; https://purl.org/pe-repo/ocde/ford#2.01.01